Hepatic Myelopathy in a Patient with Decompensated Alcoholic Cirrhosis and Portal Colopathy - Madhumita Premkumar; Avishek Bagchi; Neha Kapoor; Ankit Gupta; Gaurav Maurya; Shubham Vatsya; Siddharth Kapahtia; Premashish Kar (Case Reports in Hepatology)
Cirrhotic or hepatic myelopathy is a rare neurological complication of chronic liver disease usually seen in adults and presents as a progressive pure motor spastic paraparesis which is usually associated with overt liver failure and a surgical or spontaneous systemic portocaval shunt. We describe the development of progressive spastic paraparesis, in a patient with alcoholic cirrhosis with portal hypertension and portal colopathy who presented with the first episode of hepatic encephalopathy. The patient had not undergone any shunt procedure.